Learning to Write Case Notes Using the SOAP Format. - Cameron, Susan; Turtle-Song, Imani (Journal of Counseling & Development)
This article discusses how to use the SOAP (subjective, objective, assessment, and plan) note format to provide clear and concise documentation of the client's continuum of care. Not only does this format allow for thorough documentation, but it also assists the counselor in representing client concerns in a holistic framework, thus permitting practitioners, paraprofessionals, and case managers to better understand the concerns and needs of the client. Whereas counselors working in certain settings (e.g., public funded institutions) are likely to find various recommendations in the article easy to incorporate into their current practice, the authors believe the recommendations are relevant to a wide array of settings. Reprinted by permission of the publisher.